The Multifunctionality of a Morpheme Proposes its Morphosyntactic Features and their Specifications: Feature Matrix - Al Zahrani, Mohammad Ali (Vivid: Journal of Language and Literature, 2020)
Multifunctionality is a cross linguistic phenomenon. It refers to the linguistic capability of a linguistic form to manifest itself in different syntactic structures that result in different syntactic functions. Treating multifunctionality from a generative perspective, the paper focuses on the different functions of the Hijazi Arabic (HA) maa and contributes to the HA literature by describing these different functions and claiming that they are not instances of homonymy, but of multifunctionality. Those different functions are governed by the different syntactic environments that maa occurs in. Its occurrence in multiple syntactic environments suggests that maa has a feature matrix that includes its morphosyntactic features and their specifications that express the appropriate use and interpretation of a given structure. The findings show that maa may function as a negative particle, emphatic particle, relative pronoun, infinitival particle, conditional particle, interrogative particle, exclamative particle and a particle of inclusion. These uses differ in their syntactic flexibility and rigidity (restrictedness). Although more than one function can incorporate to express multiple senses, the salient point about the different functions of maa is that there is no semantic or syntactic ambiguity between its functions.